Synthesis of zeolites P and evaluation of their activity as new and reusable heterogeneous catalysts in a three-component ABB’ Povarov model reaction - Jefersson A. López , Robert A. Toro , Arnold R. Romero Bohórquez, Jose H. Quintana & José A. Henao (Universitas Scientiarum)
A Na-P zeolite was synthesized and subjected to ion exchange with Ca2+, Cu2+, Al3+, and In3+, and supported with H+/NH4Cl (NH4 -P) by in situ reaction of EtOH and NH4Cl. All the exchanged zeolites showed catalytic activity in the ABB’ Povarov reaction. However, zeolite NH4 -P promoted a better yield. In all reactions two products were obtained, 2,6-dimethyl-4-(2-oxopyrrolidin-1-yl)-1,2,3,4-tetrahydroquinoline and 1-(1-(4-methylphenylamino)ethyl)pyrrolidin-2-one. Synthesis using zeolite P as catalyst proves to be a simple method with high yields, short reaction times and easy preparation. The catalyst can be recovered by filtration and reused up to three times in good yields.